PERBANDINGAN AKTIVITAS BELAJAR GEOGRAFI ANTARA SISWA KELAS XI KELOMPOK PEMINATAN DENGAN LINTAS MINAT DI SMA NEGERI 1 TIGO NAGARI - Arman Arman; Slamet Rianto; Yuherman Yuherman (Universitas Negeri Gorontalo, 2022)
This research aims to determine the comparison of geography learning activities between class XI students in major and cross-major of geography at SMA N 1 Tigo Nagari. Type of this research was descriptive with a quantitative approach. The samples in this study were 30 students of class XI IPS.2, and 32 students of class XI MIPA.4. Data collection using a questionnaire. Data analysis using Independent Samples T Test. The results of this study found that sig value of Independent Samples T Test was 0.000, and the t-count value was -6.097. This means, there were differences in the geography learning activities between class XI students in major and cross-major of geography at SMA N 1 Tigo Nagari, and negative value on t-count shows that students in geographic cross-major class has a higher geographic learning activity than students in geographic major class at SMA N 1 Tigo Nagari.